2006
DOI: 10.1136/bmj.38790.468519.55
|View full text |Cite
|
Sign up to set email alerts
|

Mortality associated with delay in operation after hip fracture: observational study

Abstract: Objective To estimate the number of deaths and readmissions associated with delay in operation after femoral fracture. Design Analysis of inpatient hospital episode statistics. Setting NHS hospital trusts in England with at least 100 admissions for fractured neck of femur during the study period. Main outcome measuresIn hospital mortality and emergency readmission within 28 days. Results There were 129 522 admissions for fractured neck of femur in 151 trusts with 18 508 deaths in hospital (14.3%). Delay in op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
285
3
19

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 394 publications
(322 citation statements)
references
References 10 publications
15
285
3
19
Order By: Relevance
“…This idea is further supported by studies showing, after adjusting for patient age, gender, and comorbidities, surgical delay greater than 1 day does not lead to an increase of mortality [21,24,30,47]. However, other studies have shown, even after adjusting for comorbidities, surgical delay greater than 48 hours led to an increase in 30-day and 1-year mortality rates [7,34,37,41,50]. Despite the conflicting evidence, we support early surgical intervention in healthy patients and those with minor physiologic abnormalities and attempt to delay surgery only in patients requiring physiologic stabilization or additional preoperative workup [46].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…This idea is further supported by studies showing, after adjusting for patient age, gender, and comorbidities, surgical delay greater than 1 day does not lead to an increase of mortality [21,24,30,47]. However, other studies have shown, even after adjusting for comorbidities, surgical delay greater than 48 hours led to an increase in 30-day and 1-year mortality rates [7,34,37,41,50]. Despite the conflicting evidence, we support early surgical intervention in healthy patients and those with minor physiologic abnormalities and attempt to delay surgery only in patients requiring physiologic stabilization or additional preoperative workup [46].…”
Section: Discussionmentioning
confidence: 90%
“…Mortality rates at 30 days, 6 months, and 1 year after surgery were 6%, 18%, and 25%, respectively ( Table 1). The five patients who died during the first 30 days had an average age of 85.3 years (range, 76-94 years) and an average CCI of 4 (range, [3][4][5][6][7][8]. One 86-year-old patient with a history of prostate cancer and mitral valve repair (CCI, 3) died while in the hospital owing to pneumonia, respiratory failure, and sepsis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-one of these were excluded, 13 with insufficient data and eight that did not meet our criteria. Thus, five prospective 13-17 and 11 retrospective studies 5,6,[18][19][20][21][22][23][24][25][26] were included in our analysis. One report 17 was excluded from the analysis of 30-day mortality because of possible duplication with another study; 13 but it was included in the analysis of one-year mortality because the other study 13 was not included in this analysis.…”
Section: Resultsmentioning
confidence: 99%
“…2 Mortality associated with hip fracture is reported to be 5-10% within 30 days (short-term) and 12-37% within one year (mid-term) after surgery. [1][2][3][4] The Royal College of Physicians' guidelines recommend that surgery be performed within 24 hr after admission 5 because early (vs late) surgical repair is believed to be associated with increased survival; decreased risk of infection, venous thromboembolism or decubitus ulceration; shorter hospital stay; and fewer costs. However, a recent literature review 6 yielded conflicting results on the association between mortality and timing of surgical repair.…”
mentioning
confidence: 99%